EE230hw6solution

# Therefore obtained as

This preview shows page 1. Sign up to view the full content.

This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: ained as () ∫ ) ( ( ) ) ( ) () ( ) ( () ( ) ( ) ( ) is ) and ) The multiplication is nonzero for 0≤x≤1 and 0≤x-w≤1 therefore () ( { ) ( ) → () { fW(w) 1 -1 0 1 Since z = |w|, (z can take only positive values, the density of negative values of w will be added to absolute equivalent of that value, for example for z = ½ the density will be sum of w = ½ and w = -½ ) then ( ) ( ) will be as follows: f Z ( z) () 2 { 0 1 FZ(z) 1 () { 0 1 c) ∫( ) Alternative Solution: a-b) It is known that the pdf of sum of two independent variables is convolution of pdfs of two random variables(See Sec. 4.1 of textbook). Let W be W = X-Y therefore W can be seen as sum of X and –Y. Therefore fW(w) will be as follows: () ∫ () ( ) The multiplication is nonzero for 0≤x≤1 and 0≤x-z≤1 therefore () { ( ) This gives the same result obtained previously. ( ) ). 3) X ~N(2,1) and Y exponential with parameter 1 ( a) E(X) = 2 (first moment, mean), Var(X) = 1, ( )( ) ( ) ( ( )) E(Y) = 1= , Var(Y) = 1/ ( )( ) =1 () ( ( )) b) ( ) ( ))( (( then E(XY) = 1/2+2*1 = 5/2 ( ))) ( Correlation Coefficient = ( ) (( ) ()() () ( )) = (1/2) c) {( )} ( ) ( ) ( ) For ( ) ( ) ( ) ( ) ( ) For ( ) ( ) ( ) ( Therefore the second estimate has a lower mean square error ) ( ) 4) Given that all random variables are independent [ considered as constant since it is given): [ [∏ [ |] can be written as follows (N can be [ [ [ ∑( ⁄ ) () (⁄) For E[Y], N is no more constant and must be considered as random [[ ] [( ⁄ ) ] The MGF of the geometric r.v. () similarity between ∑ ( ) and ∑ (⁄) ( )( ∑ () ( () () ) ( ) . Once we notice the ( ), the answer is )=1/6. 5) a) The MGF (Moment Generating Function ) of obtained as follows: () ∫ { } ( which has a uniform distribution on ( ) ∫ { } ( ) is ) b) Given , it is known that the MGF of sum of independent random variables is equal to multiplication of MGF of each random variable in the sum. Therefore the MGF of Z is obtained as follows: () [ [ ( )] ( ) [ ( ) [ ( ( ) () ( ( ) ) c) The first moment of Z is obtained as follows ( )| Using L’Hopital Rule ( ( )| ) ( is obtained as we should since as R1 and R2 are identically distributed. [ [ ) )|...
View Full Document

## This homework help was uploaded on 04/06/2014 for the course EEE 230 taught by Professor Mübecceldemirekler during the Spring '12 term at Middle East Technical University.

Ask a homework question - tutors are online